Analisis Metode al-Qiraah al-Jahriyyah dalam Meningkatkan Keterampilan Membaca Teks Berbahasa Arab: al-Qiraah al-Jahriyyah - Muhammad Zaky Sya'bani; Khairil Anwar (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2020)
Many of the problems in Arabic language learning are found by students, for those who do not have Islamic educational background. SMAIT Insantama is one example of a school that has students with a diversity of previous educational background. Many students studying in the school have minimal knowledge of Arabic language, for students who have difficulty reading Arabic texts. The teachers at SMAIT Insantama tried to alleviate the problem by implementing the Al-Qiraah al-Jahriyah method as a solution to the problem. This research aims to describe the problem in SMAIT Insantama and the solutions given so that it can solve the problems that exist. And the method used is a descriptive analysis, a study with an investigation approach to upload the problem thoroughly. While the results are found with the application of al-Qiraah al-Jahriyah method students are more active in Arabic language learning and more daring to pronounce the vocabulary read. And after several meetings by implementing the method al-Qiraah al-Jahriyah students who previously did not have the mental to read the Arabic text in front of the other students is now more daring and even the degree of guilt was reduced. This is a challenge with students ' learning outcomes in their cycle tests with an increase of 9.37% or 75.25 in the 1st, 84.38 cycles of the 2nd and the 92.29 in the 3rd cycle. Thus, al-Qiraah al-Jahriyah method is very suitable to alleviate students ' problems in reading Arabic text.